1996
DOI: 10.1103/physreve.54.1478
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude equations and pattern selection in viscoelastic convection

Abstract: Pattern selection and stability in viscoelastic convection are studied in the framework of amplitude equations derived in the vicinity of stationary and oscillatory instabilities. The oscillatory instability corresponds to a Hopf bifurcation with broken translational symmetry. When this instability is the first to appear with increasing Rayleigh number, such systems may be described by coupled one-dimensional complex Ginzburg-Landau equations for counterpropagating waves. The coefficients of these equations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…In this model, the stress tensor is decomposed into both a polymeric contribution and a solvent contribution. Studies of convection in such fluids have been performed by various authors for different cases, either with freefree or rigid-rigid boundary conditions [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. It has been found that, besides the usual stationary convection, oscillatory states can also be obtained at onset.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the stress tensor is decomposed into both a polymeric contribution and a solvent contribution. Studies of convection in such fluids have been performed by various authors for different cases, either with freefree or rigid-rigid boundary conditions [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. It has been found that, besides the usual stationary convection, oscillatory states can also be obtained at onset.…”
Section: Introductionmentioning
confidence: 99%
“…By means of coupled Landau amplitude equations Martínez-Mardones et al [37] investigated the pattern selection in terms of the viscoelastic parameters. They fix Pr and E and show that increasing L stationary convection changes into standing waves by means of a subcritical bifurcation.…”
Section: Natural Convection In Oldroyd Fluidsmentioning
confidence: 99%
“…The chaotic behavior of convection of a Maxwell fluid has been investigated by Khayat [29]. [36], to study the stability of patterns in convection [37] and to investigate the convective and absolute instabilities by means of amplitude equations [38].…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the stress tensor is decomposed into both a polymeric contribution and a solvent contribution. Studies of convection in such fluids have been performed by various authors for different cases, either with free-free or rigid-rigid boundary conditions [39][40][41][42][43][44][45][46][47]. It has been found that, besides the usual stationary convection, oscillatory states can also be obtained at onset.…”
Section: Introductionmentioning
confidence: 99%